Investigation of the Thiva 2020–2021 Earthquake Sequence Using Seismological Data and Space Techniques - George Kaviris; Vasilis Kapetanidis; Spingos, Ioannis; Nikolaos Sakellariou; Andreas Karakonstantis; Kouskouna, Vasiliki; Elias, Panagiotis; Karavias, Andreas; Sakkas, Vassilis; Gatsios, Theodoros; Ioannis Kassaras; Alexopoulos, John D.; et al. (Applied Sciences, 2022)
We investigate an earthquake sequence involving an Mw = 4.6 mainshock on 2 December 2020, followed by a seismic swarm in July–October 2021 near Thiva, Central Greece, to identify the activated structures and understand its triggering mechanisms. For this purpose, we employ double-difference relocation to construct a high-resolution earthquake catalogue and examine in detail the distribution of hypocenters and the spatiotemporal evolution of the sequence. Furthermore, we apply instrumental and imaging geodesy to map the local deformation and identify long-term trends or anomalies that could have contributed to stress loading. The 2021 seismic swarm was hosted on a system of conjugate normal faults, including the eastward extension of the Yliki fault, with the main activated structures trending WNW–ESE and dipping south. No pre- or coseismic deformation could be associated with the 2021 swarm, while Coulomb stress transfer due to the Mw = 4.6 mainshock of December 2020 was found to be insufficient to trigger its nucleation. However, the evolution of the swarm is related to stress triggering by its major events and facilitated by pore-fluid pressure diffusion. The re-evaluated seismic history of the area reveals its potential to generate destructive Mw = 6.0 earthquakes; therefore, the continued monitoring of its microseismicity is considered important.